2017
DOI: 10.7554/elife.21350
|View full text |Cite
|
Sign up to set email alerts
|

Functional and mutational landscapes of BRCA1 for homology-directed repair and therapy resistance

Abstract: BRCA1 plays a critical role in homology-directed repair (HDR) of DNA double strand breaks, and the repair defect of BRCA1-mutant cancer cells is being targeted with platinum drugs and poly (ADP-ribose) polymerase (PARP) inhibitors. We have employed relatively simple and sensitive assays to determine the function of BRCA1 variants or mutants in two HDR mechanisms, homologous recombination (HR) and single strand annealing (SSA), and in conferring resistance to cisplatin and olaparib in human cancer cells. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 58 publications
12
88
1
4
Order By: Relevance
“…We investigated the importance of the BRCA1-PALB2 interaction for HR and PARPi resistance in the setting of BRCT-less BRCA1 protein expression and 53BP1 depletion. The BRCA1 L1407P missense mutation, previously shown to abrogate the BRCA1-PALB2 interaction (Anantha et al, 2017; Sy et al, 2009), was introduced into the BRCA1-ΔBRCT constructs and expressed in MDA-MB-436 cells. We confirmed that full-length BRCA1+L1407P was unable to interact with PALB2 and consequently BRCA2 and RAD51 in co-immunoprecipitation experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the importance of the BRCA1-PALB2 interaction for HR and PARPi resistance in the setting of BRCT-less BRCA1 protein expression and 53BP1 depletion. The BRCA1 L1407P missense mutation, previously shown to abrogate the BRCA1-PALB2 interaction (Anantha et al, 2017; Sy et al, 2009), was introduced into the BRCA1-ΔBRCT constructs and expressed in MDA-MB-436 cells. We confirmed that full-length BRCA1+L1407P was unable to interact with PALB2 and consequently BRCA2 and RAD51 in co-immunoprecipitation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…BRCA1 promotes the displacement of 53BP1 from chromatin surrounding DSBs and consequently activates DNA end resection (Chapman et al, 2012; Densham et al, 2016). After DNA end resection, BRCA1 directly interacts with and recruits PALB2 to DSB sites, where BRCA2-RAD51 form s a com plex with PALB2, and mutations that block the BRCA1-PALB2 interaction have been shown to reduce the efficiency of RAD51 foci formation and HR (Anantha et al, 2017; Foo et al, 2017; Sy et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 also interacts with the PALB2 protein (Sy et al 2009, Zhang et al 2009) (Figure 2), which in turn binds BRCA2 to facilitate RAD51 filament formation, a later step in HDR. Patient-derived mutations of BRCA1 that impair HDR typically also reduce SSA, another DSB repair pathway that requires end resection (Anantha et al 2017, Stark et al 2004). The exceptions are missense mutations that specifically disrupt BRCA1 interaction with PALB2, which result in reduced HDR but increased SSA, similar to BRCA2 deficiency (Anantha et al 2017, Stark et al 2004).…”
Section: Brca1 Regulates End Resection–dependent Double-strand Brementioning
confidence: 99%
“…Through these interactions, BRCA1 may have a role in fine-tuning the length of resected DNA through distinct BRCT complexes for optimal HDR function. Several missense and truncating mutations in the BRCT domain have been identified in patients, compromising multiple aspects of BRCA1 function, including damage foci localization, protein stability, and resection-dependent HDR and SSA (Anantha et al 2017, Chen et al 2017, Lee et al 2010, Li & Yu 2013, Nelson & Holt 2010). Mice carrying a Brca1 S1598F point mutation in the BRCT domain, which is analogous to the patient-derived mutation S1655F, show accelerated tumorigenesis similar to complete inactivation of Brca1 (Shakya et al 2011).…”
Section: Mechanisms Of Resistance To Poly(adp-ribose) Polymerase Imentioning
confidence: 99%
See 1 more Smart Citation